1994
DOI: 10.1111/j.1467-6427.1994.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief therapy in adult psychiatry

Abstract: Forty-one of forty-four referrals to a multidisciplinary team providing brief therapy in adult psychiatry were followed up after one year.Questionnaires were sent to attenders and their general practitioners. A good outcome was reported in 29 cases (70%) while four cases (10%) were worse. Good outcome was linked with more therapy sessions and having specific goals for treatment. Lower social class did not predict poor outcome, unlike other forms of psychotherapy. Benefit was not linked to age, sex, place of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Our team has practised solutionfocused brief therapy in the context of adult mental health for six years. In a previous study of our first three years' work (Macdonald, 1994), we reported a good outcome for 70% of our referrals and we now report results from a further cohort of referrals seen over a subsequent three-year period.…”
supporting
confidence: 57%
“…Our team has practised solutionfocused brief therapy in the context of adult mental health for six years. In a previous study of our first three years' work (Macdonald, 1994), we reported a good outcome for 70% of our referrals and we now report results from a further cohort of referrals seen over a subsequent three-year period.…”
supporting
confidence: 57%
“…Clients who came to more sessions reported better outcomes. Like many of the studies on SFT (Iveson, 1991; Macdonald, 1994, 1997; De Jong & Hopwood, 1996), it concerned adult clients and had no control group.…”
Section: Outcome Researchmentioning
confidence: 99%
“…Although earlier studies consisted of uncontrolled follow-ups of heterogeneous samples (Burr, 1993;de Shazer, 1985de Shazer, , 1991George, Iveson & Ratner, 1990;Macdonald, 1994), much of the later research used stringent designs and standardized instruments on well-defined, homogeneous samples (Cockburn, Thomas, & Cockburn, 1997;Lindforss & Magnusson, 1997;Knekt & Linfors, 2004). Numerous single case studies have also been published in the last several years.…”
mentioning
confidence: 99%